A new method to assess minimum nutrient input requirements for maize in Sub Saharan Africa - CGIAR Research Program on Maize (2019)
peer reviewed journal article that estimates that yields have to increase from the current ca. 20% of water-limited yield potential to approximately 50-75% of the potential. Minimum nutrient input requirements must rise disproportionately more, with N input increasing 9-fold or 15-fold, because current production largely relies on soil nutrient mining.